Length-weight relationship in Rasbora daniconius (Ham.) from Achancoil river, Pathanamthitta, Kerala, India - Sunil, M S (Indian Journal of Fisheries, 2011)
The relationship between length and weight in fishes is generally curvilinear. Length-weight studies in the adults and juveniles of Rasbora daniconius from September 1995 to February 1996 from Achencoil river near Pathanamthitta indicate that the relationship is significant and they show allometric growth pattern.